Realism and the Climate Crisis : Hope for Life. - Foster, John (Bristol University Press, 2022)
Hope must be mixed with realism in our approach to the climate emergency, and in this book philosopher John Foster presents a revolutionary approach to our pressing need for a habitable human future.